Elucidating the Effect of Borate Additive in High‐Voltage Electrolyte for Li‐Rich Layered Oxide Materials. Issue 11 (29th January 2022) - Li, Yixuan; Li, Weikang; Shimizu, Ryosuke; Cheng, Diyi; Nguyen, HongNam; Paulsen, Jens; Kumakura, Shinichi; Zhang, Minghao; Meng, Ying Shirley
Abstract: Lithium‐rich layered oxides (LRLO) have attracted great interest for high‐energy Li‐ion batteries due to their high theoretical capacity. However, capacity decay and voltage fade during the cycling impede the practical application of LRLO. Herein, the use of lithium bis‐(oxalate)borate (LiBOB) as an electrolyte additive is reported to improve the cycling stability in high voltage LRLO/graphite full cells. The cell with LiBOB‐containing electrolyte delivers 248 mAh g −1 initial capacity and shows no capacity decay after 70 cycles as well as 95.5% retention after 150 cycles over 4.5 V cycling. A systematic mechanism study for the LiBOB‐enabled cycling performance improvement is conducted. Analytical electron microscopy under cryo‐condition confirms the formation of a uniform interphase and less phase transformation on the LRLO particle, accompanied by less voltage decay in the cathode. The formation of B‐F species is identified in the cycled electrolyte, elucidating the HF scavenger effect of LiBOB. Due to less HF corrosion on both electrode interphases, a reduced amount of transition metal dissolution and redeposition on the graphite is proved, thereby mitigating the capacity decay in LRLO/graphite full cells. These findings suggest that the borate additive is a promising strategy to optimize high voltage electrolyte for the industrialization of LRLO. Abstract : This work reports the use of lithium bis‐(oxalate)borate (LiBOB) as an electrolyte additive to improve the cycling stability in high‐voltage LRLO/graphite full cells. The cell with the LiBOB‐containing electrolyte delivers 248 mAh g −1 initial capacity and shows no capacity decay after 70 cycles and 95.5% retention after 150 cycles. The HF scavenger effect of LiBOB in high‐voltage electrolytes is also studied with multiple advanced characterization tools in this work.